Diagnostic Value of Metagenomic Next-Generation Sequencing for Pneumonia in Immunocompromised Patients. (1st December 2022) - Li, Jun; Zhou, Chao-E.; Wei, Shan-Chen; Wang, Li-Na; Shi, Ming-Wei; Sun, Chun-Ping; Lin, Lian-Jun; Liu, Xin-Min
Abstract : Introduction . The diagnosis of pulmonary infection and the identification of pathogens are still clinical challenges in immunocompromised patients. Metagenomic next-generation sequencing (mNGS) has emerged as a promising infection diagnostic technique. However, its diagnostic value in immunocompromised patients needs further exploration. Purposes . This study was to evaluate the diagnostic value of mNGS compared with comprehensive conventional pathogen tests (CTs) in the etiology of pneumonia in immunocompromised patients and immunocompetent patients. Methods . We retrospectively reviewed 53 patients who were diagnosed with pneumonia from May 2019 to June 2021. There were 32 immunocompromised patients and 21 immunocompetent patients with pneumonia who received both mNGS and CTs. The diagnostic performance was compared between mNGS and CTs in immunocompromised patients, using the composite diagnosis as the reference standard. And, the diagnostic value of mNGS for mixed infections was further analyzed. Results . Compared to immunocompetent patients, the most commonly pathogens, followed by Cytomegalovirus, Pneumocystis jirovecii and Klebsiella pneumoniae in immunocompromised patients. Furthermore, more mixed infections were diagnosed, and bacterial-fungal-virus coinfection was the most frequent combination (43.8%). mNGS can detect more types of pathogenic microorganisms than CTs in both groups (78.1% vs. 62.5%, P = 0.016 and 57.1% vs. 42.9%, P = 0.048 ). The overall diagnostic positive rate of mNGS for pathogens was higher in immunocompromised patients (P = 0.002 ). In immunocompromised patients, a comparable diagnostic accuracy of mNGS and CTs was found for bacterial, fungal, and viral infections and coinfection. mNGS had a much higher sensitivity for bacterial infections (92.9% vs. 50%, P < 0.001 ) and coinfections (68.8% vs. 48.3%, P < 0.05 ), and it had no significant advantage in the detection of fungal infections, mainly due to the high sensitivity for Pneumocystis jirovecii in both groups. Conclusion . mNGS is more valuable in immunocompromised patients and exhibits apparent advantages in detecting bacterial and mixed infections. It may be an alternative or complementary diagnostic method for the diagnosis of complicated infections in immunocompromised patients.